Field Experiment as a Tool to Verify The Effectiveness of Prototype Track Structure Components Aimed at Reducing Railway Noise Nuisance - KRAŚKIEWICZ, Cezary; KLEKOT, Grzegorz; KSIĄŻKA, Piotr; ZBICIAK, Artur; MOSSAKOWSKI, Przemysław; CHACIŃSKA, Patrycja; AL SABOUNI-ZAWADZKA, Anna (Archives of Acoustics, 2024)
The almost unlimited possibilities of modern computational tools create the temptation to study phenomena related to the operation of engineering objects exclusively using complex numerical simulations. However, the fascination with multi-parametric complex computational models, whose solutions are obtained using iterative techniques, may result in qualitative discrepancies between reality and virtual simulations. The need to verify on real objects the conclusions obtained from numerical calculations is therefore indisputable. The enormous cost and uniqueness of large-scale test stands significantly limit the possibility of conducting tests under real conditions. The solution may be an experiment focused on testing features relevant to the given task, while minimising the dimensions of the objects under consideration. Such conditions led to the concept of conducting a series of field experiments to verify the effectiveness of prototype track components, which were developed using numerical simulations to reduce the noise caused by passing trains. The main aim of this study is to examine the acoustic efficiency of prototype porous concrete sound absorbing panels, in relation to the ballasted and ballastless track structures. Presented results of the proposed unconventional experiments carried out on an improvised test stand using the recorded acoustic signals confirm the effectiveness of the developed vibroacoustic isolators.